2023
DOI: 10.1080/03610470.2023.2253707
|View full text |Cite
|
Sign up to set email alerts
|

Appeal of the Apple: Exploring Consumer Perceptions of Hard Cider in the Northeast and Mid-Atlantic United States

Martha D. Calvert,
Clinton L. Neill,
Amanda C. Stewart
et al.

Abstract: Alcoholic or "hard" cider is experiencing a resurgence in popularity, particularly throughout the Northeast and Mid-Atlantic regions of the United States. Yet, many stakeholders struggle to understand how consumers define and distinguish hard cider amongst the sea of options in the saturated alcoholic beverage market. This study aimed to explore consumer preferences of hard cider using a phenomenological, qualitative approach. The research comprised 14 focus groups with regular cider consumers (99 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Although cider has been made in the United States since before the Revolutionary War (Flynt, 2023), a number of factors-such as Prohibition in the early 20th century and changing consumption patterns from industrialization and immigration around the same time (Lea, 2015;Watson, 2013)-led to cider's almost complete disappearance from the market between the 1940s and the early 2000s (Lea, 2015). Consequently, consumers lack the shared knowledge about prototypical flavors and their relation to ingredients and processing that is more common for beer and wine consumers (Calvert et al, 2023c). Production information analogous to that for beer and wine-whether a cider is made from Honeycrisp or Harrison apples or whether it is made from apples grown in Virginia or Vermont-does not currently carry analogous information about how that cider will taste to a potential purchaser or consumer (Calvert et al, 2023d;Fabien-Ouellet and Conner, 2018).…”
Section: Defining Hard Cidermentioning
confidence: 99%
See 2 more Smart Citations
“…Although cider has been made in the United States since before the Revolutionary War (Flynt, 2023), a number of factors-such as Prohibition in the early 20th century and changing consumption patterns from industrialization and immigration around the same time (Lea, 2015;Watson, 2013)-led to cider's almost complete disappearance from the market between the 1940s and the early 2000s (Lea, 2015). Consequently, consumers lack the shared knowledge about prototypical flavors and their relation to ingredients and processing that is more common for beer and wine consumers (Calvert et al, 2023c). Production information analogous to that for beer and wine-whether a cider is made from Honeycrisp or Harrison apples or whether it is made from apples grown in Virginia or Vermont-does not currently carry analogous information about how that cider will taste to a potential purchaser or consumer (Calvert et al, 2023d;Fabien-Ouellet and Conner, 2018).…”
Section: Defining Hard Cidermentioning
confidence: 99%
“…Thus, it is apparent that there are distinct and potentially consistent variations across cider sensory characteristics and profiles in the United States. However, it is not clear that these sensory profiles are well understood by consumers or well explained and communicated by producers (Calvert et al, 2023a(Calvert et al, , 2023c(Calvert et al, , 2023dFabien-Ouellet and Conner, 2018).…”
Section: Defining Hard Cidermentioning
confidence: 99%
See 1 more Smart Citation
“…Cider is an alcoholic beverage produced by the fermentation of apple juice. The greatest production of cider is in Europe; however, in recent years, its production has aroused an increased interest, both in Eastern European nations without a history of cider consumption and in the Northeast and Mid-Atlantic regions of the United States [1,2]. Becot and colleagues [3] reported that hard cider production has increased significantly in the United States, with an annualized growth rate of 50% between 2009 and 2014 with a total revenue of $292.5 million in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Becot and colleagues [3] reported that hard cider production has increased significantly in the United States, with an annualized growth rate of 50% between 2009 and 2014 with a total revenue of $292.5 million in 2014. The increased popularity of apple cider can be attributed to its freshness, sensory quality, and various other factors, including the territoriality, drinking occasion, and product information [2]. Furthermore, cider is rich in bioactive compounds, such as polyphenols, hydroxycinnamic acids, vitamin C, anthocyanins, and insoluble fibers [4].…”
Section: Introductionmentioning
confidence: 99%